Optimizing the Femoral Offset for Restoring Physiological Hip Muscle Function in Patients With Total Hip Arthroplasty - Hu, Xiangjun; Zheng, Nan; Chen, Yunsu; Dai, Kerong; Dimitriou, Dimitris; Li, Huiwu; Tsai, Tsung-Yuan (Frontiers in Bioengineering and Biotechnology, 2021)
Objective: Femoral offset (FO) restoration is significantly correlated with functional recovery following total hip arthroplasty (THA). Accurately assessing the effects of FO changes on hip muscles following THA would help improve function and optimize functional outcomes. The present study aimed to 1) identify the impact of FO side difference on the hip muscle moment arms following unilateral THA during gait and 2) propose the optimal FO for a physiological hip muscle function. Methods: In-vivo hip kinematics from eighteen unilateral THA patients during gait were measured with a dual fluoroscopic imaging system. The moment arms of thirteen hip muscles were calculated using CT-based 3D musculoskeletal models with the hip muscles' lines of actions. The correlation coefficient (R) between FO and hip muscles moment arms changes compared with the non-implanted hip was calculated. We considered that the FO reconstruction was satisfactory when the abductor moment arms increased, while the extensor, adductor, and flexor moment arms decreased less than 5%. Results: A decreased FO following THA was significantly correlated to a decrease of the abductor and external rotator moment arms during the whole gait (R>0.5) and a decrease of extensor moment arms during the stance phase (R>0.4). An increased FO following THA was significantly associated with shorter flexor moment arms throughout the gait (R<-0.5) and shorter adductor moment arms in the stance phase (R<-0.4). An increase in FO of 2.3 to 2.9 mm resulted in increased abductor moment arms while maintaining the maximum decrease of the hip muscles at less than 5.0%. Conclusion: An increase of 2-3 mm in FO could improve the abductor and external rotator function following a THA. Accurate surgical planning with optimal FO reconstruction is essential to restore normal hip muscle function in THA patients.